Analisis Pasal 32, 33 dan 34 KUH Perdata dalam Perspektif Fikih dan Kompilasi Hukum Islam - Yusefri Yusefri (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to find the perspective of Islamic law (fiqh) and the Compilation of Islamic Law in Chapter 32 of the Civil Code (KUH), which contains a prohibition against adultery and its partner; Chapter 33, which includes a ban on remarriage or a second time for couples whose marriage has been declared dissolved by the court, and Chapter 34 which prohibits carrying out new marriages for women who have been divorced except after three hundred days have passed. This research includes the type of jurisprudential normative legal research. Meanwhile, data analysis used descriptive qualitative, comparative, and content analysis methods through Islamic law approaches (fiqh and KHI). This study concludes that the legal provisions of Chapter 32 are very different or contradictory to fiqh and KHI. As for the requirements of chapters 33 and 34 of the Civil Code (KUH), some have differences, and others, in principle, have similarities with fiqh and KHI.